Kontribusi Persatuan Mahasiswa Islam Patani (Selatan Thailand) Di Indonesia (Pmipti) Wilayah Sumatera Barat Tahun 2017-2022 Dalam Penyelesaian Konflik Di Patani Thailand Selatan - Khoiree Yako; Dewi Dahlan (Politik Islam, 2022)
This journal discusses "The Contribution of the Patani (Southern Thailand) Islamic Student Union in Indonesia (PMIPTI) West Sumatra Region 2017-2022 in Conflict Resolution in Patani Southern Thailand". The sub-focus of the research in this thesis is what is behind the emergence of the conflict that occurred in Patani and how the contribution of PMIPTI for the West Sumatra Region in 2017-2022 in conflict resolution in Patani. The purpose of this study is to find out what is behind the emergence of conflicts that occurred in Patani and to determine the contribution of PMIPTI for the West Sumatra Region in 2017-2022 in Conflict Resolution in Patani. The type of research that the author uses in this study is a qualitative research with a descriptive approach. Sources of data used in this study consisted of primary, secondary and tertiary legal materials. The results of the author's research can be revealed that the background of the conflict in Patani, which started from the struggle for territory and power between Britain and Thailand who competed for control of the Malay Peninsula. In the end, the Thai Kingdom of Siam was able to conquer the Patani Malay Kingdom. Since the Patani Malays were under the auspices of the Thai Siamese Kingdom, the Patani people experienced a lot of discrimination, including the emergence of regulations imposed by the Thai Kingdom against the Patani people which threatened the identity of the Patani community itself. The contribution made by PMIPTI for the West Sumatra Region towards conflict resolution in Patani is by informing the outside world, especially community leaders and government officials in Indonesia regarding the problems faced by the Patani community today by carrying out various activities and opening up political space. to convey the problems of the conflict that occurred in Patani, Southern Thailand.